The American College of Rheumatology Provisional Composite Response Index for Clinical Trials in Early Diffuse Cutaneous Systemic Sclerosis. Issue 2 (February 2016) - Khanna, Dinesh; Berrocal, Veronica J.; Giannini, Edward H.; Seibold, James R.; Merkel, Peter A.; Mayes, Maureen D.; Baron, Murray; Clements, Philip J.; Steen, Virginia; Assassi, Shervin; Schiopu, Elena; Phillips, Kristine; et al.
Abstract : Objective: Early diffuse cutaneous systemic sclerosis (dcSSc) is characterized by rapid changes in the skin and internal organs. The objective of this study was to develop a composite response index in dcSSc (CRISS) for use in randomized controlled trials (RCTs). Methods: We developed 150 paper patient profiles with standardized clinical outcome elements (core set items) using patients with dcSSc. Forty scleroderma experts rated 20 patient profiles each and assessed whether each patient had improved or not improved over a period of 1 year. Using the profiles for which raters had reached a consensus on whether the patients were improved versus not improved (79% of the profiles examined), we fit logistic regression models in which the binary outcome referred to whether the patient was improved or not, and the changes in the core set items from baseline to followup were entered as covariates. We tested the final index in a previously completed RCT. Results: Sixteen of 31 core items were included in the patient profiles after a consensus meeting and review of test characteristics of patient‐level data. In the logistic regression model in which the included core set items were change over 1 year in the modified Rodnan skin thickness score, the forced vital capacity, the patient and physician global assessments, and the Health Assessment Questionnaire disability index, sensitivity was 0.982 (95% confidence interval 0.982–0.983) and specificity was 0.931 (95% confidence interval 0.930–0.932), and the model with these 5 items had the highest face validity. Subjects with a significant worsening of renal or cardiopulmonary involvement were classified as not improved, regardless of improvements in other core items. With use of the index, the effect of methotrexate could be differentiated from the effect of placebo in a 1‐year RCT ( P = 0.02). Conclusion: We have developed a CRISS that is appropriate for use as an outcome assessment in RCTs of early dcSSc.